Pengaruh Upah Minimum dan Pengangguran terhadap Kemiskinan di Sumatera Utara Periode 2005 - 2022 - Alliyah, Erina Mega; Ariwibowo, Prasetio; Nizma, Mima (Universitas Indraprasta PGRI, 2024)
This research aims to analyze the partial effects of minimum wage, unemployment, and poverty together in North Sumatra from 2005 to 2022. This research uses multiple regression analysis methods. The dependent variable in this study is poverty, while the minimum wage and unemployment serve as independent variables. The regression results indicate that the minimum wage variable, when considered individually, does not have a significant effect on poverty in North Sumatra from 2005 to 2022. Meanwhile, unemployment, when not considered individually, does have an effect on poverty in North Sumatra during the same period. The F test shows that both the minimum wage and unemployment, when considered together, have a significant impact on poverty in North Sumatra from 2005 to 2022.